Comparison of MOLLI and ShMOLLI in Terms of T1 Reactivity and the Relationship between T1 Reactivity and Conventional Signs of Response during Adenosine Stress Perfusion CMR - Esin Gezmiş; Charles Peebles; Andrew Flett; Ausami Abbas; Stephen Harden; James Shambrook (Balkan Medical Journal, 2020)
Background: One of the most important techniques of cardiac magnetic resonance in assessment of coronary heart diseases is adenosine stress myocardial first-pass perfusion imaging. Using this imaging method, there should be an adequate response to the drug adenosine to make an accurate evaluation. The conventional signs of drug response are not always observed and are often subjective. Methods based on splenic perfusion might possess limitations as well. Therefore, T1 mapping presents as a novel, quantitative and reliable method. There are several studies analyzing this newly discovered property of different T1 mapping sequences. However most of these studies are enrolling only one of the techniques. Aims: To compare modified look-locker inversion recovery and shortened modified look-locker inversion recovery sequences in terms of T1 reactivity and to determine the relationship between T1 reactivity and conventional stress adequacy assessment methods in adenosine stress perfusion cardiac magnetic resonance. Study Design: A cross-sectional study using STARD reporting guideline. Methods: Thirty-four consecutive patients, who were referred for adenosine stress perfusion cardiac magnetic resonance with suspect of myocardial ischemia, were prospectively enrolled into the study. Four patients were disqualified, and thirty patients were included in the final analysis. Using both modified look-locker inversion recovery and shortened modified look-locker inversion recovery, midventricular short axis slices of T1 maps were acquired at rest and during peak adenosine stress before gadolinium administration. Then, they were divided into six segments according to the 17-segment model proposed by the American Heart Association, and separate measurements were made from each segment. Mean rest and mean stress T1 values of remote, ischemic, and infarcted myocardium were calculated individually per subject. During adenosine administration, patients’ heart rates and blood pressures are measured and recorded every one minute. Adenosine stress perfusion images were examined for the presence of splenic switch-off. Results: There was a significant difference between rest and stress T1 values of remote myocardium in both modified look-locker inversion recovery and shortened modified look-locker inversion recovery (p<0.001). In both modified look-locker inversion recovery and shortened modified look-locker inversion recovery there was no significant correlation between T1 reactivity and heart rates response (modified look-locker inversion recovery p=0.30, shortened modified look-locker inversion recovery p=0.10), blood pressures response (modified look-locker inversion recovery p=0.062, shortened modified look-locker inversion recovery p=0.078), splenic perfusion (modified look-locker inversion recovery p=0.35, shortened modified look-locker inversion recovery p=0.053). There was no statistically significant difference between modified look-locker inversion recovery and shortened modified look-locker inversion recovery regarding T1 reactivity of remote (p=0.330), ischemic (p=0.068), and infarcted (p=0.116) myocardium. Conclusion: T1 reactivity is independent of the other stress response signs and modified look-locker inversion recovery and shortened modified look-locker inversion recovery do not differ in terms of T1 reactivity.